1969
DOI: 10.1098/rsta.1969.0031
|View full text |Cite
|
Sign up to set email alerts
|

Sound generation by turbulence and surfaces in arbitrary motion

Abstract: The Lighthill-Curle theory of aerodynamic sound is extended to include arbitrary convective motion. The Kirchhoff description of a homogeneous wave field in terms of surface boundary conditions is also generalized to surfaces in arbitrary motion. The extension is at variance with the two previously published accounts of this problem which are erroneous. When both the bounding surfaces and the turbulence are compact relative to the radiated length scales, the turbulence is acoustically equivalent to a volume di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
546
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,464 publications
(551 citation statements)
references
References 6 publications
1
546
0
4
Order By: Relevance
“…The main idea is to locate the acoustic point sources in an incompressible model and assess their energy level by means of the Lighthill tensor and in a next step, compute Green's functions of their far field radiation. Ffowcs Williams and Hawkings [14], Powell [41] and Howe [19] adopt similar approaches using the Lighthill tensor.…”
Section: Literature Summary Of Instabilities On Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…The main idea is to locate the acoustic point sources in an incompressible model and assess their energy level by means of the Lighthill tensor and in a next step, compute Green's functions of their far field radiation. Ffowcs Williams and Hawkings [14], Powell [41] and Howe [19] adopt similar approaches using the Lighthill tensor.…”
Section: Literature Summary Of Instabilities On Cavitymentioning
confidence: 99%
“…First of all, we recall the incompressible steady Navier-Stokes equations: (13) We consider the following velocity and pressure profiles: (14) The perturbed equations are deduced by introducing this velocity profile in the NS equations:…”
Section: Annex: Orr-sommerfeld Equationmentioning
confidence: 99%
“…The unilateral reductions in comparison to the standard configuration were not achieved by the beveled configuration, with the spacing in the overexpanded regime exceeding the standard configuration. Back calculation of the BSAN peak frequency assuming the convective velocity is 70 percent of the fully expanded jet velocity [63] (Eq. (2)) indicated that the relation between the configuration and the peak frequency increase was captured using this analysis method.…”
Section: Flow Fieldmentioning
confidence: 99%
“…Let r' be the density perturbation and define p' = c 2 r £ , with c being the speed of sound in the undisturbed medium. The FW-H equation is [12]:…”
Section: -Derivation Of Formulation 2bmentioning
confidence: 99%
“…To improve broadband noise prediction, a physics based methodology based on FW-H or FW -H pds equations is proposed here assuming that the detailed pressure and velocity fluctuations are known on or near the blade (FW-H eq. [12]) or on the data surface (FW -H pds eq. [13]).…”
mentioning
confidence: 99%